Lao People's Democratic Republic : Technical Assistance Report on Government Finance Statistics Mission (October 4-29, 2021). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
In consultation with the Ministry of Finance (MOF) of Lao PDR, a virtual technical assistance (TA) mission supported by the IMF's Asia and Pacific Department (APD) was conducted during October 4-29, 2021, by the IMF Statistics Department (STA) and the Capacity Development Office in Thailand (CDOT). This ongoing peripatetic capacity development mission was delivered virtually by the CDOT-based LTX with staggered remote meetings. The TA mainly worked with the Fiscal Policy and Law Department (FPLD) and the External Finance and Debt Management Department (EFDMD) on compilation of government finance statistics (GFS) and public sector debt statistics (PSDS) in line with international standards, as the agreed work plan with the authorities in the April/May 2021 TA mission.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Lao People's Democratic Republic